Evaluating Thermal Exposure Effects on Dielectric and Structural Properties of Water Treatment Residuals - Md Arfan, Muhammad Ammar Hafiz; Ismail Khan, Zuhani; Megat Ali, Megat Syahirul Amin; Ab Rahim, Siti Amalina Enche; Haddadi, Kamel; Suboh, Zulfikri (International Journal of Integrated Engineering, 2025)
Effective handling of water treatment residuals (WTRs) is essential due to their substantial volume and environmental impact. This study investigates the effects of two thermal treatment methods—microwave and oven heating—on the dielectric properties and morphological changes of WTRs. Utilizing Microwave Non-Destructive Testing (MNDT), dielectric permittivity was measured using a vector network analyzer, while morphological transformations were assessed through scanning electron microscopy (SEM). Microwave heating at power levels of 450W, 600W, and 800W resulted in a consistent increase in dielectric permittivity, ranging from 0.94 to 1.26, indicating improved dipolar alignment and material response. In contrast, oven heating produced less predictable results, with dielectric permittivity decreasing from 1.03 at 100°C to −0.55 at 200°C. SEM analysis further confirmed that microwave-treated samples exhibited more uniform structural modifications, including particle fusion and smoother surface morphology, compared to the more fragmented and heterogeneous changes observed under oven heating. The findings support the potential of microwave heating combined with MNDT as a more effective and non-invasive method for characterizing and transforming WTRs. This approach could contribute to the development of more efficient and sustainable residual management processes in the water treatment industry.